2019
DOI: 10.1002/chem.201805540
|View full text |Cite
|
Sign up to set email alerts
|

Switching the Electron‐Donating Ability of Phosphines through Proton‐Responsive Imidazolin‐2‐ylidenamino Substituents

Abstract: Stimuli‐responsive ancillary ligands are valuable tools to control the activity and selectivity of transition‐metal catalysts. The synthesis and characterization of a series of metal complexes containing phosphines with proton‐responsive imidazolin‐2‐ylidenamino substituents are reported. Determination of the ligand‐donor properties revealed that protonation of each substituent increases the Tolman electronic parameter (TEP) of the phosphine by 22 cm−1, hence allowing for switching of the electron‐donor power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 62 publications
1
19
0
1
Order By: Relevance
“…Moreover, the lower TEP value of 4 d and 6 a compared with 4 a and 6 b can be attributed to the positive inductive effect of the additional methyl group. We recently showed that the π‐donor ability of substituents R 5 strongly responds to the interaction of the exocyclic nitrogen atom with protons . To exclude that the TEP values might be influenced by such interactions with CH protons in dichloromethane, we recorded the IR spectra of the nickel complexes of phosphines 2 a , 4 a , and 4 d in the solid state.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the lower TEP value of 4 d and 6 a compared with 4 a and 6 b can be attributed to the positive inductive effect of the additional methyl group. We recently showed that the π‐donor ability of substituents R 5 strongly responds to the interaction of the exocyclic nitrogen atom with protons . To exclude that the TEP values might be influenced by such interactions with CH protons in dichloromethane, we recorded the IR spectra of the nickel complexes of phosphines 2 a , 4 a , and 4 d in the solid state.…”
Section: Figurementioning
confidence: 99%
“…Recently, we discovered that the electron‐donating ability of phosphines can be significantly increased, beyond the range of N‐heterocyclic carbenes, by attaching up to three strong π‐donating imidazoline‐2‐ylidenamino substituents to the phosphorus atom . The resulting phosphines are promising ligands in catalysis and can activate and transform chemically rather inert species such as CO 2 or SF 6 …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Fabian Dielmann (University of Münster), last featured in this section when he won a FCI Dozentenpreis in 2018, is the recipient of one of the Heinz Maier Leibnitz Prizes for 2019, presented by the German Research Foundation (Deutsche Forschungsgemeinschaft) to young scientists under the age of 40 years. Dielmann has recently published a Full Paper on switching the electron‐donating ability of phosphines in Chemistry—A European Journal …”
Section: Awarded …mentioning
confidence: 99%